A Universal and Versatile Approach for Surface Biofunctionalization: Layer‐by‐Layer Assembly Meets Host–Guest Chemistry. Issue 18 (5th August 2016) - Cao, Limin; Qu, Yangcui; Hu, Changming; Wei, Ting; Zhan, Wenjun; Yu, Qian; Chen, Hong
Abstract : A universal and versatile approach is developed using noncovalent interactions as driving forces to build bioactive surfaces with desired biofunctions. A polyanion containing guest moieties is designed as a building block to form a polyelectrolyte multilayered film via electrostatic interactions by layer‐by‐layer assembly technique, and as a matrix to provide binding sites for incorporation of biofunctional host molecules via host–guest interactions.